The association between nutritional status and motor development in children under five years old - Nurhayati Masloman; Stefanus Gunawan (Indonesian Pediatric Society, 2005)
Background Severe malnutrition in children is closely related todelayed physical growth and mental development. Very few re-ports mention the effects of mild to moderate malnutrition on mo-tor development.Objective The objective of this study was to determine the rela-tionship between nutritional status and motor development in earlychildhood.Methods In this cross-sectional study, we examined body weightof children under 5 years of age, the ability to sit or walk withoutsupport, and parachute sign in those under 2 years of age whocame to community child health surveillance posts in TumintingSubdistrict, Manado, Indonesia.Results Among 359 under-five children, 296 were well-nourishedand 63 had mild to moderate malnutrition. The ability to sit withoutsupport in malnourished children was significantly delayed com-pared to that in well-nourished ones (P=0.03). The ability to walkwithout support and parachute sign were not significantly differentbetween the two groups.Conclusion The ability to sit without support in children with mildto moderate malnutrition is delayed compared to that in well-nour-ished ones